Pengurusan Penerbitan Sertifikat Nasional Pencegahan Pencemaran (SNPP) Pada Kantor Kesyahbandaran Dan Otoritas Pelabuhan (KSOP) Oleh PT. Multi Jaya Samudera Belawan - Pantun P.A.S Lumban Gaol; Yursal Yursal; Yuna Sutria (Politeknik Pelayaran Sulawesi Utara, 2025)
This research aims to deeply analyze the process mechanism for the management and issuance of the National Pollution Prevention Certificate (SNPP) by PT. Multi Jaya Samudera Belawan at the Port Authority and Harbormaster’s Office (KSOP) Belawan. The SNPP is a crucial document that certifies a vessel’s compliance with technical and administrative requirements regulated by national laws and international conventions, specifically concerning the prevention of marine environmental pollution. The research methodology employed is a qualitative descriptive case study, focusing on direct observation of the procedural stages and interviews with relevant parties within the shipping agency and the KSOP institution. Data were collected through field observation during the fieldwork period and literature study relevant to ship certification procedures. The findings indicate that the SNPP issuance process involves a series of structured stages, beginning with the application submission, verification of supporting document completeness, followed by a physical vessel inspection by KSOP inspection officers to ensure that all pollution prevention installations and systems function according to the required standards. The final stage involves issuing the certificate once all requirements are met. Despite the established procedures, this study identified several key challenges, including: (1) Administrative Delays, which can interfere with the processing schedule; (2) Lack of Understanding among business actors regarding the latest detailed procedures, often resulting in incomplete documentation; and (3) Limited Technical Support, encompassing digital information systems or other supporting facilities. The optimization of SNPP issuance heavily relies on solid coordination between the shipping agency, ship’s crew, and the regulator (KSOP). The implications of these findings highlight the importance of regular dissemination and socialization of the latest regulations and procedures, as well as enhancing the efficiency of digital administration systems to minimize waiting times and ensure vessel compliance with marine pollution prevention standards.